Total synthesis of bistramide D - Li, Lu (2014)
The bistramides are a class of natural products isolated from the marine ascidian Lissoclinum bistratum. These molecules demonstrate significant bioactive properties, such as cytotoxicity, antiproliferative and neurotoxic activities. This thesis describes synthetic studies towards the development of the total asymmetric synthesis of one of the members, bistramide D. The structure of this natural product comprises 12 stereogenic centres and consists of three units, a tetrahydropyran (THP), an amino acid and a [6,6]-spiroketal. Building upon prior studies in our group, the synthesis of the tetrahydropyran ring has been achieved using a combination of selective cross-metathesis and an intramolecular Michael addition under kinetic control. Five different approaches were studied for the synthesis of a key intermediate, the sulfone fragment. The synthesis of the spiroketal fragment features an Au-mediated dehydrative cyclisation via a propargylic triol. The [6,6]-spiroketal unit has been successfully constructed in enantiomerically highly enriched form.